Pathogenicity of Beauveria bassiana (Balsamo-Crivelli) and Metarhizium anisopliae (Metschnikoff) isolates against life stages of Zeugodacus cucurbitae (Coquillett) (Diptera: Tephritidae) - Hintenou, M.; Omoloye, A.; Douro-Kpindou, O.K.; Karlsson, M.F.; Djouaka, R.F.; Bokonon-Ganta, A.H.; Tamò, Manuele (Springer, 2023)
Background Entomopathogenic fungi are primary pathogens that naturally affect insect pests by suppressing their populations and considered as an ecofriendly agents. The present study aimed to evaluate in vitro activity of different isolates of Beauveria bassiana and Metarhizium anisopliae against the development of larval stages of the Cucurbit fruit fly, Zeugodacus cucurbitae (Coquillett) (Diptera: Tephritidae).